2023
DOI: 10.1186/s12913-023-09515-3
|View full text |Cite
|
Sign up to set email alerts
|

Infectious disease hotlines to provide advice to general practitioners: a prospective study

Abstract: Background Telephone hotlines in infectious diseases (ID) are part of antimicrobial stewardship programs designed to provide support and expertise in ID and to control antibiotic resistance. The aim of the study was to characterize the activity of the ID hotlines and estimate their usefulness for general practitioners (GPs). Methods This was a multicenter prospective observational study in different French regions. ID teams involved in antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
2
0
0
Order By: Relevance
“…Phone consultations and informal consultations have a significant burden in the workload of AMS teams, 46 , 47 and that is confirmed in our experience. Remote consultations form a highly appreciated service by GPs 47 that improve accessibility and enhance collaboration between specialists.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Phone consultations and informal consultations have a significant burden in the workload of AMS teams, 46 , 47 and that is confirmed in our experience. Remote consultations form a highly appreciated service by GPs 47 that improve accessibility and enhance collaboration between specialists.…”
Section: Discussionsupporting
confidence: 79%
“…Phone consultations and informal consultations have a significant burden in the workload of AMS teams, 46 , 47 and that is confirmed in our experience. Remote consultations form a highly appreciated service by GPs 47 that improve accessibility and enhance collaboration between specialists. 48 A French study showed that a common motivation for phone consultations is to ‘share the emotional risk during a difficult case’, highlighting the psychological implications of antimicrobial prescription and the particular role of ID consultants.…”
Section: Discussionsupporting
confidence: 79%